2019
DOI: 10.1111/hepr.13461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment with zinc acetate hydrate in patients with liver cirrhosis complicated by zinc deficiency

Abstract: Aim: In Japan, no zinc preparation had been approved for therapeutic purposes before March 2017. Zinc acetate hydrate was recently approved for the treatment of hypozincemia. We evaluated the efficacy and safety of treatment with zinc acetate hydrate.Methods: A total of 97 patients with cirrhosis complicated by hypozincemia were treated with zinc acetate hydrate, and their serum zinc normalization rates; factors contributing to normalization; changes in blood ammonia levels; branched-chain amino acids-to-tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
(84 reference statements)
0
11
1
Order By: Relevance
“…The administration of zinc acetate dihydrate was previously predicted to reduce serum copper concentrations [ 7 ]; however, in the present study on preterm infants, there were more cases in which serum copper concentrations did not decrease. Since significant differences were observed in PMA and serum zinc concentrations before the start of administration between the groups with and without decreased serum copper concentrations, we proposed the following three mechanisms.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The administration of zinc acetate dihydrate was previously predicted to reduce serum copper concentrations [ 7 ]; however, in the present study on preterm infants, there were more cases in which serum copper concentrations did not decrease. Since significant differences were observed in PMA and serum zinc concentrations before the start of administration between the groups with and without decreased serum copper concentrations, we proposed the following three mechanisms.…”
Section: Discussioncontrasting
confidence: 73%
“…A decrease in copper concentrations has been reported as adverse effects of zinc administration [ 7 ]. The intestinal absorption of zinc and copper is performed by transporters in small intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, patients took 150 mg of polaprezinc (containing 34 mg of elemental zinc) every day. In contrast, there have been reports of copper deficiency with the long-term administration of polaprezinc and zinc acetate [61][62][63], as well as reports that caution should be exercised when using zinc acetate rather than polaprezinc [64]. In this study involving polaprezinc, there were no cases of serum copper below baseline levels and no adverse physical findings, such as anemia or neurological symptoms, were observed, including in preexcluded subjects because of their insufficiency of taking polaprezinc.…”
Section: Discussionmentioning
confidence: 59%
“…It has been suggested that zinc deficiency in cirrhosis is influenced by multifaceted factors. Poor dietary intake, maldigestion/malabsorption through gastrointestinal tract, hypoalbuminemia, excess excretion in the urine, and nutritional deficiency have been documented as possible mechanisms [2,24]. Moreover, anorexia can be induced by the intestinal mucosal atrophy due to zinc deficiency along with decrease in digestive juice secretion and impaired gastrointestinal motility [25].…”
Section: Discussionmentioning
confidence: 99%
“…Last, it is suggested that zinc ions generally bind to albumin, whereas a decrease in albumin can result in the formation of non-albuminbound zinc ions, which are excreted into the urine [32]. Therefore, cirrhotics tend to have low levels of serum albumin, and thus, are at increased risk of zinc deficiency [24,33]. To avoid this influence, we have established two multivariate models, and each incorporating index relevant Given high malnutrition risk closely relevant to zinc deficiency, and its intimate overlap with sarcopenia, we suppose it may be beneficial to combine zinc and BCAA supplementation therapy.…”
Section: Discussionmentioning
confidence: 99%